Use of point-of-care tests in pharyngotonsillitis - a registry-based study in primary health care - Jon Pallon; Katarina Hedin (Taylor & Francis Group, 2024)
Background Point-of-care (POC) tests, including C-reactive protein (CRP) tests and rapid antigen detection tests (RADT) for group A streptococci (GAS), are widely used in Swedish primary health care (PHC). This study quantifies their use in pharyngotonsillitis and explore their association with antibiotic prescribing.Material and methods Retrospective data from 2012-2016 in Region Kronoberg, Sweden, included all PHC visits with a pharyngotonsillitis diagnosis. Patient characteristics, test usage and antibiotic prescriptions were linked by visit date and personal identification number. Descriptive statistics were used for POC test analysis. Logistic regression assessed the association between CRP levels and antibiotic prescribing.Results Of 24,237 visits, 68% included RADT and 36% included a CRP test, with 89% of CRP tests performed alongside RADT. CRP testing was more frequent in patients with negative (56%) than positive RADTs (42%) (p < .001). Overall, 66% of RADTs were positive. Median CRP levels were 23 mg/l for positive RADT and 31 mg/l for negative RADT (p < .001). Antibiotics were prescribed for 95% of positive RADTs and 43% of negative RADTs (p < .001). In patients with negative RADTs, CRP testing was associated with higher antibiotic prescribing (57%) compared to no CRP testing (26%) (p < .001). Among these patients, CRP levels were associated with prescribing (aOR 1.032; 95% CI 1.029-1.035; p < .001), with 50% of prescriptions occuring at CRP levels ≤ 20 mg/l.Conclusion The use of RADTs and the proportion of positive test were higher than expected, indicating inappropriate use and diagnostic bias. CRP testing, contrary to guidelines, was common and associated with increased antibiotic prescribing.